Культовые сооружения Никония - Секерская, Н.М. (Материалы по археологии Северного Причерноморья, 2015)
The study of Nikonion cults on the basis of the available sources makes one believe that the cults of Zeus, Demeter, Kore-Persephone, Cybele, Aphrodite, Artemis, Dionysus and Heroes were worshiped in the city during the period from the VI-th to the III-rd centuries BC. The cult buildings of Nikonion consisted of three half dugouts but stone cult buildings were not excavated. In 1969 A.G. Zaginaylo excavated the clay-made altar. Their areas of distribution coincide with that of relics of the Zhabotin stage of the early Scythian period. The mid-European analogies carried out have permitted supposing an additional cultural impetus from the side of one of cultures of the Frakian haulstate, most likely the Basarab group. Analogous to altar of Nikonion have not found.